“Historical fiction is back”: (Non)Fictional Pasts and Presents in Fred Khumalo’s metahistorical romance, The Longest March - (:unkn) unknown (My University, 2023)
This article examines the ways Fred Khumalo’s second historical novel, The Longest March, blends different genres – from the use of gothic tropes to the rewriting of historical romances – to reflect on both the fabricated and limited nature of narrative, as well as its necessity in the South African context. The article concludes that The Longest March qualifies as a “metahistorical romance”, as it blurs the boundary between fiction and nonfiction while questioning historical discourse.
Keywords: African Research